Perencanaan Kebutuhan Bahan Baku Komponen Produk Bak Dump Truk Studi Kasus di PT. Ragam Mulya Abadi - Nakhas, Muhammad Iqbal; Mundari, Siti (Fakultas Teknik UMRI, 2024)
PT. Ragam Mulya Abadi, a company that produces dump truck bodies, located on Jalan Raya Menganti, Surabaya. Problems that occur in planning materials and dump truck body components are due to inappropriate production planning so that product delivery to consumers is delayed. The aproach by using Chase Strategy method used to determine production planning, then the solution is carried out using the MRP system using Lot for Lot method and it is found more economical with results of Rp. 536,550,- while with the FPR method the results obtained were Rp. 5,930,925,-. In conclusion, with the Lot for Lot method the company can save costs of Rp. 5,394,375,- compared to using FPR method. The suggestion is that companies should consider using the Lot for Lot system in procuring components for dump truck body production because it minimizes costs for the company and hoped the research results can meet future demand.